Self-organized criticality as a framework for consciousness: A review study - Walter, Nike; Hinterberger, Thilo (Frontiers in Psychology, 2022)
Objective: No current model of consciousness is univocally accepted on either theoretical or empirical grounds and the need for a solid unifying framework is evident. Special attention has been given to the premise that self-organized criticality (SOC) is a fundamental property of neural system. SOC provides a competitive model to describe the physical mechanisms underlying spontaneous brain activity and thus, critical dynamics were proposed as general gauges of information processing representing a strong candidate for a surrogate measure of consciousness. As SOC could be a neurodynamical framework, which may be be able to bring together existing theories and experimental evidence, the purpose of this work was to provide a comprehensive overview of progress of research on self-organized criticality in association with consciousness. Methods: A comprehensive search of publications on consciousness and self-organized criticality published between 1998 and 2021 was conducted. The Web of Science database was searched, and annual number of publications and citations, type of articles, and applied methods were determined. Results: A total of 71 publications were identified. The annual number of citations steadily increased over the years. Original articles comprised 50.7% and reviews/theoretical articles 43.6%. Sixteen studies reported on human data and in seven studies data was recorded in animals. Computational models were utilized in n=12 studies. EcoG data was assessed in n=4 articles, fMRI in n=4 studies, EEG/MEG in n=10 studies. Notably, different analytical tools were applied in the EEG/MEG studies to assess a surrogate measure of criticality such as the detrended fluctuation analysis, the pair-correlation function, parameters from the neuronal avalanche analysis and the spectral exponent. Conclusion: Recent studies pointed out agreements of critical dynamics with the current most influencing theories in the field of consciousness research, the global workspace theory and the integrated information theory. Thus, the framework of self-organized criticality as a neurodynamical parameter for consciousness seems promising. However, identified experimental work was small in numbers and a heterogeneity of applied analytical tools as a surrogate measure of criticality was observable, which limits the generalizability of findings.